Urban mobility with a focus on gender: The case of a middle-income Latin American city - Olivieri, Cecilia; Fageda, Xavier (Journal of Transport Geography, 2021)
This study analyzes gender differences in travel patterns for the Metropolitan Area of Montevideo, Uruguay. By applying multilevel regression models, it provides estimates of the impact of individual and contextual factors on travel behavior. The paper's findings lend support to the household responsibility hypothesis, which claims that women's travel patterns are affected by the type of household in which they live and the consequent responsibilities or roles they assume. Furthermore, gender differences in travel patterns are reinforced across census tracts. The results indicate that policy makers need to consider gender differences when seeking to enhance urban planning decisions. © 2021 Elsevier Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; déplacements urbains; environnement; géographie; géographie urbaine; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; uruguay

Rethinking social reproduction in the time of COVID-19 - Dattani, Kavita (The Journal of Australian Political Economy, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; discipline; genre; géographie; périodes historiques; ressource en ligne; sciences humaines; thématiques; travail; travail domestique; violences

Gender and water insecurity in a subarctic Indigenous community - Hanrahan, Maura; Mercer, Nicholas (The Canadian Geographer / Le Géographe canadien, 2019)
Indigenous communities in Canada suffer disproportionately from compromised water insecurity, with multiple negative implications. Some attention has been paid to gender and water insecurity in developing countries, especially in sub-Saharan Africa, but the topic has been neglected for subarctic settings. We conducted long-term research in Black Tickle, a remote Inuit community in Labrador, Canada, with no piped water and limited access to potable water. Our research was aimed at understanding the multiple dimensions of water security, identifying materialist responses, and conducting a pilot project in domestic rainwater harvesting. Water security emerged as a gendered phenomenon. We supplemented our reflective analysis on this research with two focus group discussions during which Inuit women described their experiences of water security. Participants reported that their physical and mental health are undermined by water insecurity and that water is a source of multiple stresses that demand resilience. Given a developing remittance economy, gender was identified as an increasingly significant determinant of water insecurity in this subarctic community. Having to retrieve water themselves, Inuit women experience altered gender norms and a persistent values conflict in addition to physical strain. Water acquisition is an added responsibility, impacting their labour load. Alternatively, in relying on available men to retrieve water, participants reported feeling guilty and anxious and they worried about men fetching water in dangerous weather conditions and in the vicinity of dangerous wildlife. Participants’ experiences make clear the urgency for a materialist response to water insecurity in the Indigenous subarctic.
Keywords: 2000 à aujourd'hui; accès à l'eau; amériques; canada; communauté Inuit; discipline; environnement; géographie; géographie féministe; labrador; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; thématiques

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Feeling our way: Academia, emotions and a politics of care - Askins, Kye; Blazek, Matej (Social & Cultural Geography, 2017)
Cet article a pour but de mieux comprendre le rôle des émotions dans le monde universitaire, et leur implication dans le fait de produire et de défier une université normalisée de plus en plus néolibérale. Il découle de deux discours qui mettent les émotions au premier plan dans et à travers les espaces et les pratiques universitaires, afin d’explorer de façon critique comment les connaissances et les positions sont construites et comment on les fait circuler. Il continue ensuite par prendre en compte ces questions sous l’angle de la sensibilité en tant que position politique pour être et devenir un universitaire en ces temps néolibéraux. Notre but est de contribuer à la recherche qui se développe dans le domaine des géographies émotionnelles, en amenant ce travail de manière explicite dans la conversation des débats renaissants au sujet d’une éthique de sensibilité, comme faisant partie d’une politique qui critique l’individualisme et le gestionnariat dans le monde universitaire (et au-delà). Nous examinons les façons dont les structures universitaires néolibérales font circuler certains affects particuliers, qui induisent des émotions telles que le désir et l’anxiété ainsi que l’internalisation de la compétition et de l’évaluation en tant qu’universitaires incarnés. Nos récits donnent en exemple comment les émotions et les affects qui y sont liés peuvent faire écho et se reproduire de plus en plus à travers les cultures de l’université et se propager dans les vies personnelles et professionnelles. Nous soutenons que les émotions à l’université sont importantes, coproduisant mutuellement des relations et pratiques sociales à tous les niveaux. Nous nous intéressons à leurs implications politiques et à la façon dont les normes néolibérales peuvent changer à travers des pratiques de sensibilité.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; care; discipline; europe; géographie; milieux universitaires; néolibéralisme; pratiques féministes; périodes historiques; recherche participative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; thématiques; émotions

Writing intimacy into feminist geography - Moss, Pamela; Donovan, Courtney (Taylor & Francis, 2017)
Intimacy, expressed through the feelings and sensations of the researcher, is bound up in the work of a feminist geographer. Tapping into this intimacy and including it in academic writing facilitates a grasping of the effects of power in particular places and initiates a discussion about how to access and tease out what constitutes the intimate both ethically and politically throughout the research process. This collection provides valuable reflections about intimacy in the research process - from encounters in the field, through data analysis, to the various pieces of written work. A global and heterogeneous pool of scholars and researchers introduce personal ways of writing intimacy into feminist geography. ​ As authors expand existing conceptualizations of intimacy and include their own stories, chapters explore the methodological challenges of using intimacy in research as an approach, a topic and a site of interaction. The book is valuable reading for students and researchers of Geography, as well as anyone interested in the ethics and practicalities of feminist, critical and emotional research methodologies.
Keywords: LGBTQIA2+; approches et analyses; autobiographie; discipline; ethnographie; géographie; identités LGBTQIA2+; intimité; méthodologie; queer; sciences humaines; sociologie; thématiques; émotions; éthique

Les Amériques créatives: regards croisés sur les discours et les pratiques - Pujol, Charlotte; Doré, Émilie; Drouilleau, Félicie; Villafuerte, Susana; Tinteroff Gil, Vanessa (Recherches & documents Amérique latine, 2017)
"Des civilisations précolombiennes à l'American Way of Life, les A mériques ont constitué un espace propice aux mythes et aux utopies. Terres de migrations, parfois forcées, elles sont constituées de multiples lieux de rencontres, de conflits, d'échanges culturels. Aujourd'hui les phénomènes d'innovation technologique, identitaire ou politique témoignent du fait que les Amériques, du Nord au Sud, demeurent un terreau de créativité. La créativité repose sur la capacité des acteurs à imaginer un autre cadre que celui dans lequel ils sont immergés. Aussi cet ouvrage s'attarde-t-il sur les discours et les pratiques individuels ou collectifs, discrets ou médiatisés, improvisés ou programmés qui participent à la fabrique des espaces et des sociétés. La diversité des regards et des situations analysées se traduit par la multi disciplinarité de ces pages. Sociologues, anthropologues, historiens, juristes, géographes, spécialistes de la littérature, du cinéma, du théâtre ou de la musique proposent des analyses ancrées dans la réalité ; leurs points de vue sont autant d'illustrations des processus créatifs. Il ne s'agissait pas là de chercher une improbable exhaustivité, mais bien plutôt de tenter de mettre en lumière la façon dont la force créative des individus et des groupes jalonne l'histoire et le devenir des nations américaines. C'est donc un kaléidoscope qui est proposé aux lecteurs, une diversité d'approches qui les font voyager de l'Alaska au Brésil."--Page 4 de la couverture
Keywords: DIG; agriculture; amériques; anthropologie; arts; care; corps; cours; création; danse; discipline; environnement; géographie; musique; pol4022; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques

Sur le terrain de l’émotion : déconstruire la question émotionnelle en géographie pour reconstruire son horizon épistémologique - Volvey, Anne (Carnets de géographes, 2016)
Ce texte interroge la part esthétique de la création géographique et présente des corpus et des outils théoriques et conceptuels pour travailler cette question d’épistémologie disciplinaire. Dans une première partie, il s’attache à une généalogie de l’évolution de la prise en compte du phénomène de l’émotion dans la recherche – de problème en fait significatif, puis en moyen de la connaissance géographique – à travers les réflexions conduites, notamment par la géographie féministe et qualitative anglophone, sur la méthodologie disciplinaire du terrain. Sur ce fondement, il présente les trois régimes esthétiques de savoir spatial attachés aux standards méthodologiques successivement adoptés par la discipline – régimes scopique du terrain masculiniste, linguistique et haptique du terrain féministe et qualitatif. Dans une seconde partie critique, en revenant sur le modèle du care privilégié par les géographies féministes et qualitatives pour reconstruire la politique de la méthode sur des bases relationnelles (ou intersubjectives), il traite des limites politiques rencontrées par ces géographies pour fonder pleinement un autre régime de scientificité disciplinaire à partir de l’émotion. A contrario, il montre comment la psychanalyse du care (ou psychanalyse transitionnelle) prise au sérieux, non seulement pour ses trouvailles méthodologiques et conceptuelles mais pour sa théorie relationnelle de l’identité-subjective, peut devenir l’outil d’élaboration d’une épistémologie qualitative basée sur l’émotion.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; care; corps; discipline; géographie; psychanalyse; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; émotions; épistémologie; étude qualitative

Durable mais inégalitaire : la ville - Raibaud, Yves (Travail, genre et sociétés, 2015)
Cet article interroge des projets urbains qui semblent faire consensus dans les villes européennes (pénalisation du trafic automobile intra-urbain, encouragement du deux-roues motorisé, du vélo et de la marche à pied, du tramway et des autres transports en commun, du covoiturage) du point de vue des inégalités femmes hommes, à partir d’une série de recherches menées sur l’agglomération urbaine de Bordeaux (France). L’analyse d’une enquête sur les mobilités montre en effet que les femmes seraient défavorisées par ces mesures, aussi bien en raison des tâches qui leurs sont majoritairement dévolues (accompagnement des enfants, des personnes âgées, courses etc.), par le fait qu’elles ont une moins grande habileté dans les mobilités alternatives, ou par le sentiment de leur vulnérabilité dans l’espace public (crainte de l’agression dans certains quartiers et la nuit). A qui profite la ville durable ? Comment et où se décident ses nouveaux usages ? Comment se mettent en place les changements de comportements nécessaires à cette transition vers une ville que ses promoteurs décrivent comme douce, calme, belle, apaisée ? Cet article pose l’hypothèse que les bonnes pratiques de la ville durable ressemblent fort à de nouveaux habits de la domination masculine.
Keywords: discipline; environnement; espace urbain; europe; france; géographie; projet charge mentale; régions géographiques; sciences humaines; thématiques

La ville, faite par et pour les hommes : dans l'espace urbain, une mixité en trompe-l'œil - Raibaud, Yves (Égale à égal, 2015)
Des noms d'hommes sur les plaques à tous les coins de rues. Des loisirs qui profitent en priorité aux garçons. Des offres de transport insensibles aux spécificités de genre. Sans oublier la culture du harcèlement.La ville se décline surtout au masculin. Plusieurs études récentes le confirment. L'auteur décrit comment la cité renforce les inégalités entre les femmes et les hommes et en crée de nouvelles, et montre qu'il est possible de la rendre plus égalitaire.
Keywords: discipline; domination masculine; environnement; europe; france; géographie; géographie du genre; organisation des villes; projet charge mentale; régions géographiques; sciences humaines; thématiques; violences; violences envers les femmes*

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Les Autochtones au Canada: espaces et peuples en mutation - Desbiens, Caroline; Hirt, Irène (L'Information géographique, 2012)
Alors que les questions relatives à l’autochtonie ont longtemps été le domaine de l’anthropologie, nous assistons ces dernières années à un décloisonnement des recherches. La géographie participe activement à cette mouvance, notamment par la richesse de sa boîte à outils en ce qui concerne les questions de paysage, ressources, environnement et gouvernance territoriale. En commençant par un survol des aires culturelles autochtones en Amérique, nous proposons dans cet article d’identifier trois thèmes dominants en ce qui a trait aux espaces de l’autochtonie contemporaine au Canada : la gouvernance, les savoirs, et l’urbanité.
Keywords: amériques; approches et analyses; cours; discipline; géographie; har4600; histoire et politique; pol4105; premier cycle; premières nations; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Geography and gender: Feminism and a feeling of justice - Wright, Melissa W. (Progress in Human Geography, 2010)
The recent emphasis on emotional geographies has turned critical attention to the connections linking affect and social justice. It is hard to imagine this ‘emotional turn’ in the field without much of the ground having been laid by feminist challenges to epistemology, objectivity, rationality, to the gendering of knowledge and the conceptualization of human embodiment, psychic life, subjectivity, and political agency, all in relation to power so often substantiated around a belief that the public and the private are discrete and oppositional domains necessary for organizing social, economic, and political life. In this report, I address the following questions. How can feminist and emotional geography tighten their connections, fuel their shared passions and generate a synergy of scholarship oriented toward activism and progressive change? How can geographies of feeling broaden the path for justice that feminism endeavors to plow? In doing so, I continue my emphasis on research that grounds theoretical discussion with research conducted in activist projects conducted in the name of social justice. I do so as a matter of my own emotional investments – I firmly believe that scholarship must engage with the ways in which people beyond the academy wrestle with the concepts in their daily lives that scholars contemplate, sharpen, and circulate through academic production. So the debates that we scholars so often have with ourselves over the finer points of theory reveal, in my view, their greater significance when they provide tools useful for people who seek to create kinder and more compassionate worlds. Thus, I highlight the scholarship that creates toolkits out of feminist scholarship, emotional geographies, and research on social justice.
Keywords: approches et analyses; care; discipline; genre; géographie; justice sociale; militance; ressource en ligne; sciences humaines; thématiques; travail; travail du care; émotions

Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

Geography and gender: what belongs to feminist geography? Emotion, power and change - Sharp, Joanne (Progress in Human Geography, 2009)
Keywords: approches et analyses; discipline; discours dominant; genre; géographie; ressource en ligne; sciences humaines; systèmes d'oppressions; émotions

Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques

«Je pensais que je pourrais avoir une relation plus egalitaire avec un Europeen.» Le rôle du genre et des imaginaires geographiques dans la migration des femmes - Riaño, Yvonne; Baghdadi, Nadia (Nouvelles Questions Féministes, 2007)
Le nombre de femmes migrant vers la Suisse en provenance de pays extérieurs à l'Union européenne a considérablement augmenté ces dernières années. La féminisation de la migration a été conceptualisée dans la littérature comme une conséquence des forces économiques mondiales et comme la seule option pour les femmes des pays à faible revenu pour résoudre leurs besoins matériels. Cet article soutient que cette perspective est insuffisante pour expliquer la migration féminine. Sur la base d'une analyse qualitative des récits de vie de vingt femmes d'Amérique latine, d'Europe du Sud-Est et du Moyen-Orient, nous concluons que de nombreux facteurs autres que les difficultés économiques influencent les décisions des femmes de migrer. En particulier, le désir d'atteindre l'égalité des sexes dans la société au sens large et au niveau du ménage semble être une forte motivation à la migration. Les images positives de l'Europe, des Européens et des relations de genre en Europe favorisent des pays comme la Suisse comme destination de migration. Nous concluons que lorsque les femmes traversent les frontières, elles construisent et reconstruisent le genre, et que le genre façonne leurs schémas migratoires.
Keywords: cours; discipline; environnement; europe; femmes immigrantes; géographie; géographie du genre; récits de vie; régions géographiques; sciences humaines; soc1061; sociologie; suisse; thématiques; travail

The nature of gender: work, gender, and environment - Nightingale, Andrea (Environment and Planning D: Society and Space, 2006)
Le genre est depuis longtemps reconnu comme important dans les questions environnementales, mais la manière de conceptualiser le lien entre genre et environnement fait l’objet de nombreux débats. Les théories féministes sur les femmes et le genre ont évolué, tout comme les conceptualisations sur le genre et l’environnement, ce qui a donné lieu à un débat clé au sein de l’écoféminisme et des littératures associées sur la question de savoir s’il existe une relation essentielle ou contingente entre les femmes et les environnements naturels. En géographie, la plupart des écologistes politiques partent du principe que le lien entre genre et environnement est une relation contingente, et étudient donc la manière dont les relations de genre sont saillantes dans la construction symbolique et matérielle des questions environnementales. Dans cet article, je cherche à m’appuyer sur ce travail et à soulever à nouveau la question de la manière dont le genre est conceptualisé par rapport à l’environnement. Je commence par passer brièvement en revue certains des travaux qui ont été réalisés sur le genre et l’environnement, puis je m’inspire du féminisme post-structural pour suggérer que le genre lui-même a été sous-théorisé dans les travaux sur l’environnement. Une fois que le genre est reconceptualisé en tant que processus, la relation dynamique entre le genre, l’environnement et d’autres aspects de la vie sociale et culturelle peut être mise en évidence. Il en ressort que les écologistes politiques doivent examiner la question du genre au-delà du foyer et de la communauté, et reconceptualiser le lien entre le genre et l’environnement. Une étude de cas sur la foresterie communautaire au Népal est utilisée pour illustrer l’importance d’interroger les processus par lesquels les relations entre les sexes deviennent saillantes et sont reproduites symboliquement et matériellement.
Keywords: approches et analyses; asie; discipline; environnement; géographie; histoire et politique; népal; politique écologique; post-structuralisme; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; écoféminisme

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Les femmes autochtones au Canada : profil statistique d'après le recensement de 2006 - Affaires autochtones et développement du Nord Canada (2002)
Sommaire : points saillants de la situation des femmes autochtones au Canada. Structure de la population et lieu de résidence : •• En 2006, les femmes autochtones en Ontario représentaient environ 11 % de l’ensemble de la population d’identité autochtone. 31 % des femmes autochtones vivaient dans les provinces de l’Ouest (Manitoba, Saskatchewan, Alberta et Colombie‑Britannique). •• En 2006, l’âge médian de la population autochtone était de 27 ans, contre 40 ans pour la population non autochtone, une différence de 13 ans. Les résultats de l’étude révèlent que chez les Indiens inscrits vivant dans les réserves, un peu plus de femmes (44 %) que d’hommes (35 %) étaient âgés de 19 ans et moins. En comparaison, le pourcentage des Indiens inscrits vivant hors réserve âgés de 19 ans et moins était un peu plus élevé tant chez les femmes (45 %) que chez les hommes (43 %). De plus, de tous les groupes d’identité autochtone, c’est chez la population inuite féminine (49 %) et masculine (46 %) que se trouvait la proportion la plus importante des 19 ans et moins. •• La population féminine autochtone vieillit, quoique à un rythme plus lent que la population féminine non autochtone. En 2006, les femmes de 60 ans et plus représentaient plus de 7 % de l’ensemble de la population d’identité autochtone. Utilisation et connaissance des langues •• Les résultats de l’étude révèlent que la majorité des femmes autochtones, soit 73 %, ont appris l’anglais comme langue maternelle, tandis que seulement 16 % ont d’abord appris une langue autochtone et 8 %, le français. La proportion de filles et de femmes autochtones dont la langue maternelle est une langue autochtone (langue amérindienne ou inuktitut) est relativement faible dans les groupes d’âge plus jeunes, et plus élevée dans les groupes d’âge plus âgés. L’anglais prend donc plus d’importance que les langues autochtones et le français au fil du temps. •• La proportion de la population de langue maternelle autochtone est plus élevée chez les Inuites. Un plus grand nombre de femmes inuites de tous les groupes d’âge, soit 65 %, indiquent que l’inuktitut est leur langue maternelle, contre 32 % pour l’anglais. Chez 28 % des Indiennes inscrites, la langue maternelle est une langue autochtone; la proportion est beaucoup plus faible chez les Métisses, à 3 %. •• La vaste majorité (75 %) des Autochtones parlent principalement l’anglais à la maison, alors que 16 % parlent une langue autochtone et 5 %, le français. En outre, 29 % des membres des Premières nations affirment qu’ils peuvent parler une langue autochtone suffisamment bien pour tenir une conversation. La proportion est cependant beaucoup plus élevée chez les membres des Premières nations vivant dans les réserves. En 2006, la moitié des membres des Premières nations vivant dans les réserves (51 %) pouvaient s’exprimer dans une langue autochtone, contre 12 % de ceux qui vivaient hors réserve. Les langues des Premières nations les plus répandues en 2006 étaient le cri (87 285), l’ojibway (30 255), l’oji‑cri (12 435) et le montagnais‑naskapi (11 080).
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; démographie; famille; femmes* autochtones; géographie; histoire et politique; intersectionnalité; langue; langues autochtones; maternité; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; thématiques; transmissions; éducation; étude démographique

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques